2018
DOI: 10.1253/circj.cj-17-1001
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Subcutaneous Cardioverter Defibrillator in Patients at High Risk of Sudden Cardiac Death ― Primary Japanese Experience ―

Abstract: S-ICD is a safe and effective alternative to conventional TV-ICD. The long-term safety and efficacy of the S-ICD need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…In contrast, we only used signals classified as sensed ("S" marker) that would result in device shocks. Given the much lower rates of IAS due to MPI noted in the present study and in previous reports, [11][12][13][14] the specificity of this test likely is very low.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In contrast, we only used signals classified as sensed ("S" marker) that would result in device shocks. Given the much lower rates of IAS due to MPI noted in the present study and in previous reports, [11][12][13][14] the specificity of this test likely is very low.…”
Section: Discussioncontrasting
confidence: 63%
“…We previously reported that the incidence of IAS due to MPI was 5%. 13 Interestingly, Theuns et al 9 reported fewer IAS events due to noncardiac oversensing with SMART Pass. However, the cause of IAS was not provided in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient experienced an adequate shock during follow-up. Therefore, the S-ICD system’s defibrillation efficacy was confirmed by the success rate of defibrillation tests [ 15 ]. Implantation of the S-ICD intramuscularly could be long-lasting, is safe concerning infection, and is the best alternative to the standard subcutaneous placement [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…Implantable cardioverter defibrillators (ICD), encompassing both transvenous (TV‐ICD) and subcutaneous types (S‐ICD), act as a safeguard against life‐threatening ventricular tachyarrhythmias. S‐ICD has proven advantageous for certain patients, such as those at an elevated risk of ICD infection and those who do not necessitate pacing, and are widely used worldwide, including Japan 1–4 . Postoperative pain is a distinctive challenge associated with S‐ICD implantation which can sometimes be severe and significantly influences the quality of the patient journey 5 .…”
Section: Introductionmentioning
confidence: 99%
“…S-ICD has proven advantageous for certain patients, such as those at an elevated risk of ICD infection and those who do not necessitate pacing, and are widely used worldwide, including Japan. [1][2][3][4] Postoperative pain is a distinctive challenge associated with S-ICD implantation which can sometimes be severe and significantly influences the quality of the patient journey. 5 The substantial pain is arguably due to the larger size of the device and the pocket required for it.…”
mentioning
confidence: 99%